Therapeutic management of odontogenic abscess in maxillofacial area in patient confirmed covid-19: A case report and literatur review - Andi Tajrin (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of writing this case report and literature review is to discuss the management of therapy in covid-19 patient with odontogenic abscess in the maxillofacial area.Method: A 65-year-old male patient came to the Ibnu Sina Makassar Hospital, complaining of swelling of the right submandibular blood extending to the buccal, sublingual, submental, and temporal. Patient was in a limp condition, shortness of breath (dyspnea), coughing, difficulty opening his mouth, difficulty eating and swallowing with pulse 121 times / minute, breathing 32 times / minute, and oxygen saturation of 94% (simple mask of 5 lpm). Patient was diagnosed with the right submandibular abscess extending to the right buccal, right temporal, right and left sublingual, and submental with sepsis due to gangrene of tooth root 46. Surgical incision and drainage of the abscess was performed under general anesthesia.Results: Incision and drainage of the abscess in the patient was carried out even with the suspicion that the patient was indicated as having been exposed to covid-19 by following the principle of preventing covid-19 infection.Conclusion: Surgical preparation, appropriate therapeutic management, and proper use of PPE will help provide the best service to patients while protecting medical personnel in the current Covid-19 pandemic era.